The Third Gulf War and its impact on GermanAmerican relations - Kadhum Suhil, Athmar (International Journal of Psychosocial Rehabilitation, 2020)
The third Gulf War constituted an important turning point in the nature of German-American relations, and for the first time since the end of the Second World War, Germany took a position opposing the American position, so that the pattern of the relationship between the two parties shifted from the type of relationship based on the policy of the subordinate to that of the relationship based on isolation and opposition before the German side towards the US policy towards Iraq. For the first time in the history of relations between the two countries, economic interests, especially with the Arab East, constitute a point of contention and tension between the two parties. Therefore, this study aims to reveal the nature and causes of this shift in the nature of the relationship between the two countries by answering the following questions: - Was the completion of the German unity, with its geographical, demographic, and economic impact, the reason for the Germans devising a foreign policy independent of the United States of America? - Berlin’s desire, after being freed from the restrictions of dependency on the American foreign decision, to assume the leadership of Europe far from the American intervention through its opposition to the policy of aggression against Iraq in 2003.